Agricultural biotechnology: Potential, challenges, and debate - Marjorie R. Lundgren; Amanda P. Cavanagh; Philip Macnaghten (Plants, People, Planet)
With a rapidly expanding human population, urbanization, poverty, and threats from climate change, new innovations are needed to achieve global food security and nutrition requirements in a just and sustainable manner. Agricultural biotechnology has the potential to achieve step changes in crop productivity and nutritional content to meet these needs whilst minimizing agricultural environmental impacts, but critical questions remain on how the technology is developed and used, and for whom. This special collection collates the latest thinking in natural and social sciences surrounding agricultural biotechnology to help engage, enrich, and stimulate debate, and inform policy.